Genotype and metabolic profile associations in athletic adaptation to physical loads - Alaverdyan, D. A.; Namozova, S. S.; Shcherbak, S. G.; Urazov, S. P.; Glotov, O. S. (Theory and Practice of Physical Culture, 2019)
Studies of energy metabolism specifics in athlete`s body under heavy varied-intensity physical workloads made it possible to find the genetic determinants associated with the training process. Different genes are known to be of influence on the key functions of energy metabolism. Frequency of alleles favorable for some physical quality building (e.g. endurance) is higher in athletes versus untrained people and may reach maximums in the sport leaders. Sampled for our study of the genetic and biochemical factors of influence on the athletic adaptation to physical workloads were 71 sporting students aged 20 on average and specialized in 11 sports. We used the PCR-PDRF analysis to identify genotypes for 9 genes including ACE (rs4340), PPARA (rs4253778), PPARD (rs2016520), PPARG (rs1801282), PPARGC1A (rs8192678), AMPD1 (rs17602729), ACTN3 (rs1815739), DRD2A (rs1800497) and HTR2A (rs6313). We also tested the cardiovascular system functionality and blood biochemistry of the sample. The study found no meaningful intergroup differences in the trained versus untrained groups. We confirmed and supplemented the functional associations of PPARGC1A and ACE genes with the physiological and biochemical test rates to discuss the gene polymorphism triggered by physical trainings.